Rheumatoid arthritis with aquaporin-4 antibody-positive neuromyelitis optica receiving rituximab therapy - Chrong Reen Wang,; Sheng-Min Hsu,; Ying-Chen Chen, (Archives of Rheumatology, 2022)
A spectrum of autoimmune diseases has been associated with optic neuritis or myelitis in the presence of aquaporin-4 (AQP4) antibody, creating a classification named neuromyelitis optica spectrum disorder (NMOSD).[1] Further studies have identified a pathogenic role of B cells,[2] and rituximab (RTX) is an effective and safe treatment in this disease.[3] Herein, we report a case of rheumatoid arthritis (RA) with anti-AQP4-positive optic neuritis. The RTX therapy resulted in absent autoantibody and clinical improvement. A 58-year-old Han Chinese woman visited our hospital with a five-year history of polyarthritis and visual impairment. She was diagnosed to have RA with recent therapy including methotrexate (MTX) 10 mg/week and prednisolone 5 mg/day. For ocular presentations, there was retro-orbital pain with bilateral papillitis, followed by blurred vision with delayed responses/low amplitudes in visual evoked potential, leading to a diagnosis of optic neuritis. Nevertheless, she did not attend to the ophthalmological follow-up without taking medications, resulting in a progressive eyesight loss to a counting fingers vision (10/5 cm, right/left). Physical examination at the rheumatology clinic showed swollen, tender joints over wrist, metacarpophalangeal, proximal interphalangeal, and knee areas. Conventional X-ray demonstrated erosion over the wrist. Erythrocyte sedimentation rates (ESR, 52 mm/h) and C-reactive protein (CRP, 11.9 mg/L) levels were elevated with a 5.88 Disease Activity Score-28 (DAS28). Autoantibody profiles had increased anti-AQP4 (11 U/mL, enzyme-linked immunosorbent assay, RSR Limited, UK), rheumatoid factor (RF, 105 IU/mL) and anti-cyclic citrullinated protein (anti-CCP, 28 U/mL) levels. Evaluation for systemic lupus erythematosus (SLE) showed normal hemogram and negative urine analysis, as well as anti-nuclear antibody negativity, antidouble-stranded deoxyribonucleic acid, and anti-Sm antibodies. Sjögren's syndrome survey revealed negative SSA/SSB antibodies and minor salivary gland biopsy. There was no demyelination on brain/spinal cord magnetic resonance imaging. The patient was diagnosed with NMOSD associated with anti-AQP4-positive optic neuritis and an autoimmune disease RA.[4,5] She had refractory RA activity under MTX 15 mg/week, prednisolone 5 mg/day, and sulfasalazine (SAZ) 2 g/day. Conventional X-rays demonstrated erosions over right wrist, proximal interphalangeal and metacarpophalangeal joint areas with joint space narrowing over wrists (Figure 1). The RTX therapy with a regimen of 1 g x two fortnightly infusions every six months was initiated from 2016, with a total of 20 infusions until the end of 2020. There were completely depleted circulating CD19-positive B cells (0/µL) after two infusions, normalized ESR/CRP levels with a reduced DAS28 to 2.99 after four infusions, followed by negative anti-AQP4 (1 U/mL, normal reference below 3 U/mL), anti-CCP (below 7 U/mL), and RF (below 20 IU/mL) levels. She had an improved ophthalmological vision to decimal visual acuity 0.06/0.04 (right/left) in 2019. After 20 infusions, the DAS28 further improved to 2.10 and MTX doses were tapered to 7.5 mg/week without using SAZ. Except for initial infusion-related reactions, no adverse effects were observed during RTX therapeutic period. A written informed consent was obtained from the patient for all diagnostic and therapeutic procedures. <f1> Despite an extending spectrum of rheumatology disorders associated with NMO, including antiphospholipid syndrome, primary Sjögren's syndrome, SLE, and systemic sclerosis, there is no inclusion of RA.[5,6] An investigation of NMOSD identified juvenile RA as a coexistent autoimmune disorder,[7] and a survey on optic neuritis showed a poor visual outcome associated with RA.[8] Interestingly, a case with overlap syndrome involving RA and polymyositis was diagnosed to have NMOSD with the presence of anti-AQP4-positive longitudinal myelopathy.[9] Notably, in Han Chinese, genetic polymorphisms have been demonstrated to be shared among RA, NMOSD, and AQP4-seropositivity.[10] In conclusion, in this report, we present an anti-AQP4-positive RA case with optic neuritis, which may raise a potential to incorporate RA into the autoimmunity spectrum in NMOSD.